Little cruelties - Nugent, Liz (Scout Press, 2020)
"An uneasy but powerful read from bestselling author Liz Nugent that delves into the darkness visited upon a family of three working-class Irish brothers, exploring the ways in which families can wreak emotional damage across generations and doom men to give in to their own worst impulses in service to a culture that has abandoned them"--